2015
DOI: 10.1002/acr.22481
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet and Incidence of Rheumatoid Arthritis in Women

Abstract: Objective We examined the association between Mediterranean dietary pattern as measured by Alternate Mediterranean Diet Score (aMed) and risk of incident rheumatoid arthritis (RA) in US women. Methods We prospectively followed 83,245 participants from the Nurses’ Health Study (NHS, 1980–2008) and 91,393 participants from NHS II (1991–2009) who were initially free of baseline connective tissue diseases. Dietary information was obtained via validated food frequency questionnaires (FFQ) at baseline and approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 43 publications
2
81
0
3
Order By: Relevance
“…A recent Japanese study found that the anti-CCP antibody could cross-react with microbial proteins and plants, not only limited to human autoantigens. This observation supports the hypothesis of food or microbes inducing RA via anti-CCP antibody production [1,38,39].…”
Section: Potential Therapeutic Role Of Gut Microbiotasupporting
confidence: 89%
“…A recent Japanese study found that the anti-CCP antibody could cross-react with microbial proteins and plants, not only limited to human autoantigens. This observation supports the hypothesis of food or microbes inducing RA via anti-CCP antibody production [1,38,39].…”
Section: Potential Therapeutic Role Of Gut Microbiotasupporting
confidence: 89%
“…43 44 Finally, legumes, nuts and whole grains, which are abundant in dietary fibre and antioxidants may have potential to mitigate the RA risk. 33 In the current study, we have found that the protective effects of higher diet quality on RA risk are strongest among women aged ≤55 years. This result is similar to our previous finding that the positive association between obesity and RA is also restricted among women with RA diagnosed at younger age.…”
Section: Discussionmentioning
confidence: 49%
“…In our previous study evaluating association of Alternate Mediterranean Diet Score (AMED) with RA risk, we did not observe a significant association of AMED score as well as the fruit and vegetable consumption components with overall RA risk, but did not investigate whether this was associated with earlier onset RA. 33 AMED is the simple sum of nine dichotomised components at median, not including detailed amount of actual dietary intakes. We previously found another AHEI-2010 component, sugar-sweetened beverages, to be linked to increased risk of later onset RA (diagnosed after age 55 years) using different comparison groups from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Total average energy/day was calculated as the sum of average energy/day from all 120 items. Participants reporting extreme total average energy/day (men <800 kcal/day or >4,200 kcal/day, women <600 kcal/day or >3,500 kcal/day) were excluded (n = 10) . Thus, the range of total average energy intake/day was 800–4,200 kcal/day for men, and 600–3,500 kcal/day for women.…”
Section: Methodsmentioning
confidence: 99%